NATURAL DISASTER AND MITIGATION ENCYCLOPEDIA BOOK BASED ON ISLAMIC VALUES FOR ELEMENTARY STUDENTS - Kirana Prama Dewi; Nabila Ulfah (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2021)
This research aims to determine feasibility for the natural disaster and its mitigation based on Islamic Values for elementary school students. This study uses the research and development (RD) method, the model used in the research is the ADDIE model. This stage of development is analyze, design, development, implementation, and evaluation. The subject of the research trials is 36 students of grade IV and V SD Muhammadiyah Pakel Program Plus Yogyakarta. Data collection techniques are interviews, observations, and the teacher and student response assessment sheets are then analyzed using quantitative and qualitative data. Media Feasibility Assessment results by media experts acquiring a score of 4, material expert 3.9, learning expert 3.88, and linguist 3.50. Besides, a small-scale student response with a score of 97.5 and a large-scale student response with a score of 97.8. Based on some assessments, the average value of 95.1 was achieved with the "excellent" category. Based on this assessment, the category "Very Feasible" was obtained. The response from the teacher obtained from an extensive questionnaire obtained good results starting from the presentation of the material, the layout, the colors used, as well as the pictures/illustrations presented. From these results, it can be concluded that the natural disaster and its mitigation based on the Islamic values encyclopedia are appropriate for learning.